Analysis of the Role of Notaries in Consumer Protection in Property Transactions - Sanny Estera; Benny Djaja (Jurnal Indonesia Sosial Sains, 2023)
Property transactions are one of the most complex and high-risk transactions for consumers. In property transactions, notaries have an important role in ensuring the validity and protection of consumer rights. However, there have not been many studies that specifically discuss the role of notaries in consumer protection in the context of property transactions. The purpose of this study is to analyze the role of notaries in consumer protection in property transactions. This research utilizes qualitative research methods. Data was collected through in-depth interviews with notaries, and literature study analysis. The data obtained from interviews and literature studies are analyzed qualitatively. Data analysis will involve the process of coding, grouping findings, and discovering themes that emerge from the data. The results show that the notary's role as an independent and neutral party responsible for checking and confirming the legality of property documents, facilitating secure payments, and providing legal advice to consumers is very important in safeguarding consumer interests and protection